Local and Global Stability of Compact Leaves and Foliations - Zhukova, N.I. (Журнал математической физики, анализа, геометрии, 2013)
The equivalence of the local stability of a compact foliation to the completeness and the quasi analyticity of its pseudogroup is proved. It is also proved that a compact foliation is locally stable if and only if it has the Ehresmann connection and the quasianalytic holonomy pseudogroup. Applications of these criterions are considered. In particular, the local stability of the complete foliations with transverse rigid geometric structures including the Cartan foliations is shown. Without assumption of the existence of an Ehresmann connection, the theorems on the stability of the compact leaves of conformal foliations are proved. Our results agree with the results of other authors. Доказана эквивалентность локальной устойчивости произвольного компактного слоения полноте и квазианалитичности его псевдогруппы голономии. Мы доказали, что компактное слоение локально устойчиво тогда и только тогда, когда оно допускает связность Эресмана и имеет квазианалитическую псевдогруппу голономии. В качестве приложения показана локальная устойчивость полных компактных слоений с жесткой трансверсальной структурой, включающих в себя полные картановы слоения. Без предположения о существовании связности Эресмана доказаны теоремы о стабильности компактных слоев конформных слоений. Установлена связь с результатами других авторов.